Design, Development and Evaluation of Celecoxib-Loaded Microsponge-Based Topical Gel Formulation - V. Kadam, Vishruti; I. Patel, Vrutti; S. Karpe, Manisha; J. Kadam, Vilasrao (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2016)
Background: Microsponges is a class of polymeric microspheres that are porous and are aimed to deliver a pharmaceutically active constituent competently at the smallest dose and also, to alter release of the drug. Objective: The aim of the present work was to formulate a topical gel based drug delivery system of microsponges containing Celecoxib (CXB). Method: Quasi emulsion solvent diffusion method was used to prepare microsponges. The inner phase of formulation (drug dissolved in polymer solution) was added drop-wise into outer phase of Polyvinyl Alcohol (PVA) solution at room temperature. Microsponges were obtained after stirring for 3 hours. Drug loaded microsponges, dispersed in propylene glycol, were added to soaked carbopol and mixed thoroughly. Final pH was adjusted by triethanolamine. Final formulation was evaluated for particle size, % entrapment efficiency, % production yield, surface morphology, % drug release, drug content, rheological behaviour, in vitro skin permeation etc. Results: Microsponges of optimized batch were spherical, fine and free flowing. The optimized formulation showed % practical yield of 72.84 ± 1.34, % entrapment efficiency of 82.4 ± 1.48 and mean particle size of 26.4 μm. The optimized batch incorporated in gel showed pH of 6.1, 12.35 grams-cm/sec of spreadability, 99.06 % of drug content and 68.1 % drug release. Skin permeation studies concluded that the drug was released in a controlled manner for a period of 12 hours. The optimized batch was found to be appropriately stable. Conclusion: The CXB loaded in a microsponge based gel was found to have good appearance, other micromeritic properties and entrapment efficiency along with controlled in vitro release profile of drug.
Keywords: solvent diffusion